Air Pollution A Comprehensive Perspective - Haryanto, Budi (IntechOpen, 2012)
The links between air pollutants and health impacts are many and complex. The environmental health community is being challenged to take stronger mitigation to respect population health and is taking opportunities to further their implication. Recognizing, observing, and analyzing exposures are a promising way forward, but also raise a myriad of new challenges and questions, including what such approaches are, when and how they can put into practice, and what their implications are for protecting human health. This book gives an overview of key issues in air pollution. Reviews and research papers describe air pollution in a variety of context, such as: evolution of air pollutant, urban structure effects, exposure in agriculture, surface ozone monitoring, the respiratory diseases impacts, appropriate technology, and response management to the air pollution.